Association of FTO variants with BMI and fat mass in the self-contained population of Sorbs in Germany - Tönjes, A; Zeggini, E; Kovacs, P; Böttcher, Y; Schleinitz, D; Dietrich, K; Morris, A; Enigk, B; Rayner, N; Koriath, M; Eszlinger, M; Kemppinen, A; et al. (2010)
The association between common variants in the FTO gene with weight, adiposity and body mass index (BMI) has now been widely replicated. Although the causal variant has yet to be identified, it most likely maps within a 47 kb region of intron 1 of FTO. We performed a genome-wide association study in the Sorbian population and evaluated the relationships between FTO variants and BMI and fat mass in this isolate of Slavonic origin resident in Germany. In a sample of 948 Sorbs, we could replicate the earlier reported associations of intron 1 SNPs with BMI (eg, P-value0.003, Β0.02 for rs8050136). However, using genome-wide association data, we also detected a second independent signal mapping to a region in intron 2/3 about 40-60 kb away from the originally reported SNPs (eg, for rs17818902 association with BMI P-value0.0006, Β0.03 and with fat mass P-value0.0018, Β0.079). Both signals remain independently associated in the conditioned analyses. In conclusion, we extend the evidence that FTO variants are associated with BMI by putatively identifying a second susceptibility allele independent of that described earlier. Although further statistical analysis of these findings is hampered by the finite size of the Sorbian isolate, these findings should encourage other groups to seek alternative susceptibility variants within FTO (and other established susceptibility loci) using the opportunities afforded by analyses in populations with divergent mutational and/or demographic histories. © 2010 Macmillan Publishers Limited All rights reserved.